ANALYSIS OF MISALIGNED PROFITS AND TAX RISKS FROM AGGREGATED AND ANONYMISED COUNTRY-BY-COUNTRY REPORT - Andreas Rossi Dewantara (Scientax, 2022)
Indonesia faces a 15.6% decline in tax revenues due to the COVID-19 pandemics. As fiscal headroom tightens, the tolerance for international tax avoidance will decrease and globally untaxed income will be prioritised. As a part of 2020-2024 Strategic Plan, DGT intends to carry out tax administration reforms through the development of Compliance Risk Management (CRM). This study attempts to highlight the potential of Country-by-Country Report (CbCR) data to be used in CRM. We propose two methodologies to assess tax risks, using misaligned profits and OECD tax risk assessment indicators. In both measures, Australia, Cayman Islands, Iraq, Malaysia, Niger, and Singapore are flagged as risky jurisdictions, which could be used to inform CRM function to prioritize auditing affiliated party transaction related to these jurisdictions. The methodologies outlined here could also be replicated for individual CbCR data to create a risk profile that is more tailored to each MNE group.